2020
DOI: 10.3390/ijms21197152
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Antioxidants in the Brain

Abstract: The brain is vulnerable to excessive oxidative insults because of its abundant lipid content, high energy requirements, and weak antioxidant capacity. Reactive oxygen species (ROS) increase susceptibility to neuronal damage and functional deficits, via oxidative changes in the brain in neurodegenerative diseases. Overabundance and abnormal levels of ROS and/or overload of metals are regulated by cellular defense mechanisms, intracellular signaling, and physiological functions of antioxidants in the brain. Sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
154
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(183 citation statements)
references
References 208 publications
(246 reference statements)
1
154
0
2
Order By: Relevance
“…In addition, K reportedly has neuroprotective activities against OS injury induced by H 2 O 2 in SH-SY5Y cells [ 17 ]. Both types of reported anti-ROS activity of CKs could potentially explain to effects of c ZR , K3G, and iPR in reduction of superoxide radicals in the SAL-induced SH-SY5Y cell PD model [ 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, K reportedly has neuroprotective activities against OS injury induced by H 2 O 2 in SH-SY5Y cells [ 17 ]. Both types of reported anti-ROS activity of CKs could potentially explain to effects of c ZR , K3G, and iPR in reduction of superoxide radicals in the SAL-induced SH-SY5Y cell PD model [ 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…ROS production is majorly initiated by cellular metabolisms in organelles, including mitochondria, peroxisome, lysosome, endoplasmic reticulum, and plasma membrane [ 94 ]. Among the oxidative species, the superoxide and hydrogen peroxide are known to be the major sources to induce the oxidative damages in various brain disease models [ 122 ]. The accumulation of ROS can further initiate the production of reactive nitrogen species (RNS), as well as inflammation, in the central nervous system (CNS) [ 123 ].…”
Section: Central Hypothesis For Ad Pathogenesismentioning
confidence: 99%
“…The accumulation of ROS can further initiate the production of reactive nitrogen species (RNS), as well as inflammation, in the central nervous system (CNS) [ 123 ]. In the normal conditions, the metabolic pathways of misfolded proteins or extracellular pathogens trigger the ROS/RNS production followed by the antioxidation maintaining homeostasis in brains serving neuroprotective roles [ 122 , 123 ]. These antioxidants involve the ROS scavengers (e.g., ascorbic acid (AA), proline, etc.…”
Section: Central Hypothesis For Ad Pathogenesismentioning
confidence: 99%
“…Endogenous antioxidant systems, such as those comprising superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione, play an important role in the rescue of brain cells from OS and preserve the correct redox balance in the brain tissue, by stimulating antioxidative defense mechanisms for counterbalance ROS. These enzymatic antioxidants are chainbreaking antioxidants that can scavenge radical species [6]. Manganese-containing SOD decreases the superoxide radical anion produced during the electron transport chain in the mitochondrial matrix, whereas CAT and/or GPx play key roles in decomposinghydrogen peroxide to water and oxygen [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These enzymatic antioxidants are chainbreaking antioxidants that can scavenge radical species [6]. Manganese-containing SOD decreases the superoxide radical anion produced during the electron transport chain in the mitochondrial matrix, whereas CAT and/or GPx play key roles in decomposinghydrogen peroxide to water and oxygen [6,7]. Various studies have reported decreased levels of antioxidative enzyme activities, such as CAT and SOD, in neurological diseases including PD [8,9].…”
Section: Introductionmentioning
confidence: 99%